Radiocarbon Investigation of the Solitary African Baobab from Dalkut, Dhofar, Oman - PATRUT, Adrian; RATIU, Ileana Andreea; AL HINAI, Abdulrahman R.; AL FARSI, Khalid A.; RAKOSY, Laszlo; BROWN, J. Jed; AL HARTHY, Laila S.; MOLNAR, Mihaly; PATRUT, Roxana T.; BODIS, Jenő (Studia Universitatis Babeș-Bolyai Chemia, 2024)
The article discloses the AMS (accelerator mass spectrometry) radiocarbon dating results of the well-known African baobab of Dalkut, Dhofar Governorate, Oman. The investigation shows that the baobab has a cluster structure and is composed of 3 perfectly fused stems. Three wood samples were collected from primary branches and one sample was collected from the exterior of a stem. Eight tiny segments were extracted from the samples and dated by radiocarbon. The oldest dated sample segment, which originates from a primary branch of the southern stem, had a radiocarbon date of 590 ± 18 BP, which corresponds to a calibrated age of 685 ± 15 years. This result indicates that the southern stem of the baobab of Dalkut is 800 ± 30 years old. According to other radiocarbon dating results, the two northern stems are younger and emerged from the southern stem around 550 years ago. The tree of Dalkut is a solitary baobab. The nearest baobab is over 150 km away, to the north